Wilhelm Lübke (1826 - 1893) : Aspekte seines Lebens und Werkes - Axtmann, Alexandra; Gawlik, Ulrike (2019)
The German art and architecture historian and art critic WilhelmLübke (1826-1893) taught at the important 19th century polytechnics in Berlin, Zurich and Stuttgart. From 1885 until his death, he was also Professor of Art History at the Karlsruhe Polytechnic, now the Karlsruhe Institute of Technology (KIT). This publication provides an insight into the biography and career of Wilhelm Lübke as well as a comprehensive list of his writings.